Ultrasonic-assisted extraction for flavonoid compounds content and antioxidant activities of India Moringa oleifera L. leaves: Simultaneous optimization, HPLC characterization and comparison with other methods - Lin, Xue; Wu, Lingfeng; Wang, Xiong; Yao, Linling; Wang, Lu (Journal of applied research on medicinal and aromatic plants, 2021)
In this work, the performance of ultrasonic-assisted extraction (UAE) in simultaneously enhancing the total flavonoid content (TFC) and antioxidant activities of India Moringa oleifera L. leaves (MOLs) was analyzed by using response surface methodology (RSM). Based on the results of the single-factor experiment, a three-factor five-level central composite design (CCD) was proposed. RSM results indicated that the liquid to solid ratio had an evident effect on all responses, while the ultrasonic powder had no significant influence on them. The measured parameters obtained under the optimal conditions were consistent with the predicted results. The analysis of variance results revealed that TFC and antioxidant activities reached the optimal values under ultrasonic power of 188 W, liquid to solid ratio (L/S) of 40:1, and ethanol concentration of 52%. Moreover, it was verified via a comparative study that the extract extracted by optimized ultrasonic extraction (OUAE) exhibited higher TFC and antioxidant activities than that extracted by stirring-assisted extraction (SAE), soxhlet-assisted extraction (SOAE) or microwave-assisted extraction (MAE). The results showed that compared with the extracts obtained by using other extraction methods, OUE extracts included eight flavonoid compounds with the high levels of d-(+)-catechin (10.92 mg/g MOLs DW), hyperoside (10.26 mg/g MOLs DW) and kaempferol-3-O-rutinoside (4.85 mg/g MOLs DW). In conclusion, UAE could effectively enhance the TFC and antioxidant activities of MOLs, which provides theoretical basis for upgrading the large-scale industrial and medicinal applications.